Penerapan Pembelajaran Berbasis Gamifikasi Menggunakan Quizizz Dalam Mata Pelajaran Electrical - Hsb, Heni Saskiah; Yanto, Doni Tri Putra (Jurnal Pendidikan Teknik Elektro, 2025)
This study aims to analyze the implementation and effectiveness of gamification-based learning using the Quizizz platform in the Electrical subject at SMK Penerbangan Nusantara Ketaping. The research was motivated by the low student engagement, limited variation in teaching methods, and the lack of optimal integration of technology in the learning process. The research employed a quasi-experimental method with a Non-Equivalent Control Group Design, involving an experimental class using Quizizz and a control class applying conventional methods. The research instruments consisted of validated pre-test and post-test questions to measure students' learning outcomes. The data analysis results indicated a significant improvement in the experimental class compared to the control class, as evidenced by normalized gain (N-Gain) and t-test results. These findings suggest that the use of gamification-based digital media such as Quizizz is effective in enhancing students’ engagement and learning outcomes, while also creating a more interactive, enjoyable, and relevant learning experience aligned with vocational education needs.